A Social Realist Perspective: A quest for understanding quality practices in higher education - Masehela, Langutani M (South African Journal of Higher Education, 2016)
Key words: quality assurance, critical realism, social realism, analytical dualism, morphogenetic approach In this paper I argue that, for a focus on the enhancement of teaching and learning to have its intended positive impact, a ‘close-up’ look or contextualised understanding of the way academics work with conceptions of quality and the policies and procedures that are intended to promote it are necessary. The paper proposes that research located in Bhaskar’s critical realism and Archer’s social realism provides a means of producing these understandings. This kind of research is important because, in spite of the introduction of quality assurance into South African higher education, the system continues to be plagued by poor performance reflected not only in low success and graduation rates with high attrition rates but also in the poor quality of graduates. As such, this has led the body responsible for quality assurance, the Higher Education Quality Committee (HEQC) to embark on the next cycle of its work which focusses specifically on teaching and learning.